Hubungan Perilaku Pencegahan Dengan Kejadian Diabetes Mellitus Pada Lansia - Boekoesoe, Lintje; Halid, Apriyanto; Ahmad, Zul Fikar; Nurdin, St. Surya Indah; Katili, Rusli A (Madu : Jurnal Kesehatan, 2023)
The elderly are vulnerable to health problems due to the aging process. The deterioration of the function of body cells (degenerative) and the decline in the function of the body's immune system so that degenerative diseases appear, one of which is Diabetes Mellitus. The study aimed to determine the relationship between preventive behavior and the incidence of Diabetes mellitus in the elderly. This type of research is an analytical survey with a cross-sectional study approach. The study population was all older adults suffering from Diabetes Mellitus at the Dungingi Health Centre, with as many as 94 people using data collection techniques using a questionnaire. Data analysis using the Chi-Square test. The results showed a relationship between preventive behavior and the incidence of Diabetes mellitus in the elderly with a p-value of 0.001. It is concluded that there is a relationship between preventive behavior and the incidence of Diabetes mellitus in the elderly. It is hoped that in the future, the elderly can improve diabetes prevention behavior.